2007
DOI: 10.1093/gerona/62.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use at the End of Life Among Older Adults: Does It Vary by Age?

Abstract: Background. Issues around end-of-life health care have attracted increasing attention in the last decade. One question that has arisen is whether very elderly individuals receive overly aggressive treatment at the end of life. The purpose of this study was to address this issue by examining whether health care use at the end life varies by age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
7
40
1
2
Order By: Relevance
“…Hospital use tended to increase rapidly in the last months of life, the same has been found in previous studies (e.g. Mukamel et al 2002;Klinkenberg et al 2005;Menec et al 2007). The number of hospital inpatient days began to rise earlier for the youngest age a Inpatient days at a university hospital, general hospital, and health centre for those who had <90 inpatient days at a health centre in the last 2 years of life b Days at a residential home, in housing with 24-h assistance for older people, and at a health centre for those who spent !…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hospital use tended to increase rapidly in the last months of life, the same has been found in previous studies (e.g. Mukamel et al 2002;Klinkenberg et al 2005;Menec et al 2007). The number of hospital inpatient days began to rise earlier for the youngest age a Inpatient days at a university hospital, general hospital, and health centre for those who had <90 inpatient days at a health centre in the last 2 years of life b Days at a residential home, in housing with 24-h assistance for older people, and at a health centre for those who spent !…”
Section: Discussionsupporting
confidence: 88%
“…In a German study, Bickel (1998) found that, with increasing age at death, the use of residential homes and ambulatory services rose steeply, whereas the probability of hospital treatment decreased with advancing age. Also a recent Canadian study (Menec et al 2007) showed that very old individuals (85+ years old) were more likely to be cared for in longterm-care institutions and less likely to be hospitalised than younger olds. The major differences in health and social service use between age groups once again indicate that neither in research nor in practice should old people be considered to be a single group; rather, even the population aged !…”
Section: Discussionmentioning
confidence: 99%
“…A USA-study, examining expenditure among decedents enrolled in the standard fee-for-service Medicare program in 1996 showed that the number of hospital and ICU admissions, the use of ventilators, of pulmonary artery monitors, of dialysis, and of cardiac catheterization decreased for persons aged ≥85 years as compared to those aged 64-84 years [4]. These and other authors therefore concluded that patients of 85 years old or older are less likely to receive aggressive care at the end-of-life [4][5][6]. Moreover, a survey on endof-life decision-making practices in six European countries revealed that non-treatment decisions were most frequently made for patients aged 80 or older [7].…”
Section: Introductionmentioning
confidence: 99%
“…For det første viser studier at de som dør tidlig ofte dør av sykdommer og skader som krever mer sykehusressurser enn dem som dør i høy alder (15). For eksempel dør mange av ulike former for kreft relativt tidlig, spesielt kvinner, mens personer i eldre aldersgrupper oftere dør av hjerteinfarkt (16).…”
Section: Diskusjonunclassified
“…Det er ofte gode medisinske grunner til dette, ettersom eldre pasienter ikke tåler like tøff behandling som yngre pasienter, men litteraturen antyder at det også kan vaere elementer av aldersdiskriminering (16,18). Ytterligere studier er nød-vendig for å kartlegge dette.…”
Section: Diskusjonunclassified